Myocardial adaptation and efficiency in response to intensive physical training in elite speedskaters - Poh, K. K.; Ton-Nu, T. T.; Neilan, T. G.; Tournoux, F. B.; Picard, M. H.; Wood, M. J. (International Journal of Cardiology, 2007)
Physiological cardiac adaptations to exercise training resulting in the `athlete's heart` are well known. Most of these studies, however, were included either those who exercise to exhaustion, non-elite athletes or those who participate primarily in sports requiring extensive weight training. Studies utilizing conventional and tissue Doppler echocardiographic studies in highly competitive elite athletes whose training includes both aerobic and weight training are limited.